Test method for characterising the thermal protective performance of fabrics exposed to flammable liquid fires - Kemp, S.E.; Annaheim, S.; Rossi, R.M.; Camenzind, M.A. (Fire and materials, 2017)
Summary People, such as emergency service and military personnel, require protection from fires involving flammable liquids and liquefiable solids (Class B fires) in a number of situations. Fires involving flammable liquids typically reach higher temperatures sooner when compared to other types of fuel, yet there appears to be little literature that specifically investigates the protective performance of fabrics against such fires. Therefore, a new method was developed to enable the characterisation of the protective performance of fabrics when exposed to flammable liquid fires. Fabric samples were mounted on a sample plate inclined to three different angles of incidence. Known volumes of hydrocarbon fuel were pipetted into a fuel reservoir, ignited, then tipped onto fabric samples. Ten thermocouples embedded in the sample plate measured the resultant change in temperature at the technical rear of the fabric samples throughout the exposure. Significant differences were observed between fabrics for maximum temperature, time to maximum temperature, maximum heat flux, transferred energy and estimated burn risk. Therefore, this new methodology enabled discrimination among fabrics based on the protection they provide. Differences were also observed when the volume of fuel and the angle of incidence varied and, therefore, these device settings must be controlled for repeatable results. Copyright © 2016 John Wiley & Sons, Ltd.